RITUAL HAJI MASYARAKAT SASAK LOMBOK: RANAH SOSIOLOGIS-ANTROPOLOGIS - Fahrurrozi Fahrurrozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
Philosophy of Kaâ€˜bah no arak lek dalam ate represents a shift intradition and culture among Sasak people from tradition which is symbolized itself with Rinjani mountain to Kaâ€™bah symbol of purification and soul purification. This shift made hajj and Kaâ€™bah become the top ceremony which connect man and Allah, in religious and culture level. The Kaâ€™bah symbolic in life philosophy and Sasak culture which is come from hajj perform spiritualisation in sociocultural and local political Sasak community. Through this symbolisation, their tradition is not only refelected religiously but also reflected in the norms and custom which becomes culture base of Sasak people. By the people, those things is formulated into â€œadatâ€, andâ€tata krameâ€. Tipaâ€™ Kaâ€˜bah as a religious philosophy is based on Islam and explain hajj as a continuous ritual by perform hajj in Mekah. For Sasak community, before someone performs hajj, they have to train their heart in good deeds. After the finish the hajj, they also have to keep their heart by manifested it through social activities. Sasak people calls the ritual as â€œbehajiâ€.